Investigation of obsolete diversity of rye (Secale cereale L.) using multiplexed SSR fingerprinting and evaluation of agronomic traits - Targonska-Karasek, Malgorzata (J Appl Genet, 2020)
Common rye (Secale cereale L.) is one of the most important cereals in Europe. Nevertheless, its germplasm collections are among the least numerous compared with cereals. There are only about 27,000 Secale accessions in 70 gene banks around the world. Despite extensive research on the molecular characterization of genetic resources, only a fraction of this collection has been described. The main objective of the presented study was to perform genotypic and phenotypic characterization of an obsolete gene pool represented by 100 accessions originated from 28 countries around the world and preserved in the gene bank of the Polish Academy of Sciences Botanical Garden – Center for Biological Diversity Conservation in Powsin. Genetic analysis using simple sequence repeat markers showed that the obsolete gene pool is relatively large. This indicates that different sources of variability were used in breeding programs. However, the genetic variation is in no way related to the place of origin. Despite the great differences in the genetic make-up, the collection showed a broadly common phenotype. This could result in a low level of interest among breeders in the stored germplasm, undervalued as a source of important but not easily observable traits, e.g., high disease resistance, which was found in some accessions. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13353-020-00579-z) contains supplementary material, which is available to authorized users.